ANALISIS ASUHAN KEPERAWATAN INTERVENSI INOVASI ISOMETRIC HANDGRIP EXERCISE TRAINING PADA PASIEN DENGAN HIPERTENSI HIPERTENSI DI IGD RS BHAYANGKARA TK. I R. SAID SUKANTO - Aldin Aditya Fareza, (2022)
Hypertension is the highest risk factor that causes death worldwide. The incidence of hypertension continues to increase because people are used to living an unhealthy lifestyle and symptoms that do not arise, that's why hypertension is often called the silent killer. The implementation of this activity is to analyze the effectiveness of the Isometric Handgrip Exercise Training innovation intervention on reducing blood pressure in hypertensive patients in the Emergency Unit Bhayangkara Tk. I R. Said Sukanto Hospital. After performing the innovation intervention with a frequency of twice, it showed that there was a change in systolic blood pressure with an average decrease of 5 mmHg. Based on the analysis of the innovation intervention, it can be concluded that the Isometric Handgrip Exercise Training therapy provides significant changes in the blood pressure of hypertensive patients